How does emotional intelligence predict driving behaviors among non-commercial drivers?. (February 2022) - Ahmed, Jubaer; Ward, Nicholas; Otto, Jay; McMahill, Annmarie
Highlights: Emotional intelligence predicted dangerous driving behaviors. Lower emotionality increased dangerous driving behaviors. State and federal administrations should promote emotional intelligence. Emotional intelligence should be included in driving education and traffic safety programs. Abstract: Dangerous driving behaviors have been found to be a leading contributor to vehicle crashes and fatalities, with more than 2.7 million people injured and 36, 560 people killed in the United States in 2018 (NHTSA, 2020 ). Drivers' emotions have been found to be among the leading contributors to dangerous driving behaviors. Emotions can be measured and understood through one's emotional intelligence (EI). Previous research has confirmed the relationship between EI and dangerous driving behaviors among general driving populations in limited scope. This study analyzed dangerous driving behaviors (e.g., aggressive driving) among non-commercial US drivers. 615 US drivers ages 18 to 65 (M = 31.14, SD = 11.15) with valid US driver's licenses (non-commercial) participated in this study. Participants completed an online survey through Qualtrics that included the Trait Emotional Intelligence Questionnaire (TEIQue-SF) to measure different dimensions of EI and the Dula Dangerous Driving Index (DDDI) and the Driving Behavior Questionnaire (DBQ) to measure dangerous driving behaviors. Furthermore, participants reported their demographic information, including age, sex, and location. Correlation analysis revealed that significant associations exist between dangerous driving behaviors and EI. The emotionality component of EI was found to be the strongest predictor of dangerous driving behaviors. The findings concluded that participants with higher EI scores engaged in less dangerous driving behavior, resulting in fewer crashes and fatalities. Thus, promoting and improving EI may be useful in preventing risky driving among non-commercial drivers. Incorporating emotional intelligence education in driver's education, workplace training, and licensing procedures can be helpful to develop safer drivers. Further research is needed to investigate commercial drivers' behaviors in relation to EI.